1979
DOI: 10.1113/jphysiol.1979.sp012625
|View full text |Cite
|
Sign up to set email alerts
|

Non‐electrolyte permeability of trout gills: effect of temperature and adrenaline

Abstract: SUMMARY1. The gill permeability to various non-electrolytes (P.) was measured in freshwater and sea-water adapted trout (Salmo gairdneri). This study was performed in vitro using a 'head-perfused' preparation. The influence of temperature and adrenaline (10-6 M) on permeability to non-electrolytes was also investigated. 4. Adrenaline has no effect on Pmannitol and Pdextran, but increases Pbutano1 and Water selectively according to the adaptation medium (+ 160 % and + 100 % in fresh water and + 25 % and + 20 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The results presented indicate the existence of different pathways across the gills as a function of the physico-chemical properties of the non-electrolyte, and thus support the original hypothesis (Isaia, 1979) concerning different pathways for the various molecules: (a) a secondary lamellar pathway for small molecules, (b) a paracellular pathway for molecules the size of mannitol and (c) an extrusion pathway for hexose polymers in primary lamellae.…”
Section: Non-electrolyte Pathways In Trout Gillssupporting
confidence: 83%
See 1 more Smart Citation
“…The results presented indicate the existence of different pathways across the gills as a function of the physico-chemical properties of the non-electrolyte, and thus support the original hypothesis (Isaia, 1979) concerning different pathways for the various molecules: (a) a secondary lamellar pathway for small molecules, (b) a paracellular pathway for molecules the size of mannitol and (c) an extrusion pathway for hexose polymers in primary lamellae.…”
Section: Non-electrolyte Pathways In Trout Gillssupporting
confidence: 83%
“…Two results point to the complexity of the relationship between structure and function in the bronchial epithelium. (1) The gills possess a very impermeable epithelium compared to other tight epithelia (Isaia et al 1978 a) especially in sea water where shallow junctions exist between chloride cells (Isaia, 1979). (2) In the course of transfer from fresh water to sea water the bronchial permeability decreases for water, (Isaia, Payan & Girard, 1979), increases for mannitol and remains constant for dextran (Tables 2 and 3).…”
Section: Non-electrolyte Pathways In Trout Gillsmentioning
confidence: 99%
“…Therefore, the decrease of PCP uptake rates with increasing salinity (Table 2), which is most prominent in the low salinity range, may be due to the decline of water flux accompanied by the increase of environmental salinity. During seawater acclimation, the gill permeability to small molecules such as ethanol and buthanol decreased, that to molecules the size of mannitol increased, and that to large molecules such as dextran stayed constant (Isaia 1979(Isaia , 1982. The developing chloride cell and its arm allows the tubular reticulum and extracellular space to communicate with the external milieu via leaky junctions (Sardet et al 1979).…”
Section: Discussionmentioning
confidence: 98%
“…Isaia etal. (1978b) and Isaia (1979) speculate that branchial permeability may be similarly increased to the respiratory gases oxygen, carbon dioxide and un-ionized ammonia. In freshwater fish, epinephrine also stimulates excretion of ionized ammonia, uptake of sodium and maintenance of acid-base balance (Girard & Pavan 1980).…”
Section: Qualitative Studies: Pathogenesis Of Branchial Lesionsmentioning
confidence: 97%
“…Stress-mediated release of epinephrine may be the key element in compensating for loss of surf ace area. Isaia, Girard & Payan (1978a), Isaia,Maetz& Haywood (1978b) and Isaia (1979) have shown that epinephrine increases branchial permeability to the lipophilic substance butanol and to water and urea. Isaia etal.…”
Section: Qualitative Studies: Pathogenesis Of Branchial Lesionsmentioning
confidence: 98%